Penerapan Hukum Pidana Atas Kelalaian Berkendaraan yang Menyebabkan Kematian Menurut UU Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan (Studi Kasus: Pengadilan Negeri Kotamobagu) - Setiawan, Alicia Dwi Wulandari; Mumpuni, Niken Wahyuning Retno (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study discusses the application of criminal law to the negligence of motor vehicle drivers resulting in death, based on the provisions of Law Number 22 of 2009 concerning Traffic and Road Transportation (LLAJ Law), specifically Article 310 paragraph (4). This study focuses on a case study at the Kotamobagu District Court by examining several decisions that show differences in judges' decisions regarding criminal acts that have similar elements of offenses. This study aims to examine the application of the theory of culpa and the theory of criminal responsibility in assessing negligence, as well as assessing the consistency of judges' legal considerations. The method used is normative juridical with a statutory approach and decision studies. This study also links the theory of culpa as the basis for error and the theory of criminal responsibility to assess the extent to which negligence can be subject to criminal sanctions. The results of the study show that despite the similarities in the forms of negligence, judges impose different sanctions based on considerations such as the level of error, the defendant's attitude, and the victim's contribution. This shows the importance of the presence of the principles of justice, legal certainty, and benefit in criminal decisions. This study recommends revising articles related to traffic crimes and strengthening jurisprudence so that the application of the law is more consistent and fair.